Analysis of the Indonesian Men’s Volleyball Team Match in the 2025 SEA Games Final - Ahmad Fa'iq Arsyad Fahreza; Aziz Amrulloh (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to analyze the defense and offense performance of the Indonesian and Thai Men's National Volleyball Teams in the 2025 SEA Games Final. The method used is descriptive quantitative with a non-experimental approach through observation of video recordings of the match accessed via the RCTI Sports YouTube channel. The analysis focused on defense aspects, including receiving, digging, and blocking, as well as offense aspects, including serving, open spikes, quick attacks, back attacks, and tosses. The results showed that it was a close match, with Thailand winning 3-2 (25-20, 16-25, 25-23, 23-25, 15-12). Indonesia excelled in quick attack (83.3%), toss (97.5%), and receive (94.5%), but had weaknesses in blocking with a success rate of only 41.1%. Conversely, Thailand showed more consistent performance with effective blocks (58.3%), minimal serve errors (87.2%), and stability in the deciding sets. The key factors in Thailand's victory were the harmonious integration of defense and attack, as well as the ability to minimize unforced errors. This study contributes to the development of volleyball performance analysis at the international level and provides practical implications for coaches in designing integrated training programs that emphasize a balance between defense and attack.